Oxaliplatin-induced changes in microbiota, TLR4+ cells and enhanced HMGB1 expression in the murine colon. - Vanesa Stojanovska; Rachel M McQuade; Sarah Fraser; Monica Prakash; Shakuntla Gondalia; Rhian Stavely; Enzo Palombo; Vasso Apostolopoulos; Samy Sakkal; Kulmira Nurgali (PLoS ONE)
Oxaliplatin is a platinum-based chemotherapeutic used for cancer treatment. Its use associates with peripheral neuropathies and chronic gastrointestinal side-effects. Oxaliplatin induces immunogenic cell death by provoking the presentation of damage associated molecular patterns. The damage associated molecular patterns high-mobility group box 1 (HMGB1) protein exerts pro-inflammatory cytokine-like activity and binds to toll-like receptors (namely TLR4). Gastrointestinal microbiota may influence chemotherapeutic efficacy and contribute to local and systemic inflammation. We studied effects of oxaliplatin treatment on 1) TLR4 and high-mobility group box 1 expression within the colon; 2) gastrointestinal microbiota composition; 3) inflammation within the colon; 4) changes in Peyer's patches and mesenteric lymph nodes immune populations in mice. TLR4+ cells displayed pseudopodia-like extensions characteristic of antigen sampling co-localised with high-mobility group box 1 -overexpressing cells in the colonic lamina propria from oxaliplatin-treated animals. Oxaliplatin treatment caused significant reduction in Parabacteroides and Prevotella1, but increase in Prevotella2 and Odoribacter bacteria at the genus level. Downregulation of pro-inflammatory cytokines and chemokines in colon samples, a reduction in macrophages and dendritic cells in mesenteric lymph nodes were found after oxaliplatin treatment. In conclusion, oxaliplatin treatment caused morphological changes in TLR4+ cells, increase in gram-negative microbiota and enhanced HMGB1 expression associated with immunosuppression in the colon.